The Role of the Ministry of Home Affairs Through the Disaster Resilient Subdistrict Program (KENCANA) as a Disaster Mitigation Effort in Supporting National Security - Arif Fikri Fauzan; Syamsunasir; I Dewa Ketut Kerta Widana; Rachmat Setiawibawa; Anwar Kurniadi (Cita konsultindo, 2025)
Indonesia faces high disaster risk due to its geographical position in the ring of fire and tropical climate. Disaster mitigation is a strategic necessity to maintain social stability and national security. The Ministry of Home Affairs (Kemendagri) launched the Disaster Resilient Subdistrict Program (KENCANA) to strengthen subdistrict capacity in facing disaster threats. Through a literature review, this article examines the role of Kemendagri in implementing KENCANA and its contribution to risk mitigation and national security. The results of the study show that Kemendagri's active involvement in training subdistrict heads and cross-sector coordination increases the effectiveness of mitigation and local resilience, which has an impact on strengthening national security. Challenges in implementation were found in limited resources and coordination, which can be overcome by increasing human resource capacity and multi-stakeholder collaboration